Adeno-associated viral glutamate decarboxylase expression in the lateral nucleus of the rat hypothalamus reduces feeding behavior - Noordmans, A J; Song, D K; Noordmans, C J; Garrity-Moses, M; During, M J; Fitzsimons, H L; Imperiale, M J; Boulis, N M (Gene therapy, 2004)
In vivo gene transfer of glutamate decarboxylase (GAD) has been explored as a means of inducing or increasing the production of the inhibitory amino-acid neurotransmitter, GABA. This strategy has been applied to neuroprotection, seizure prevention, and neuromodulation. In the present experiment, AAV2 was used to transfer the genes for green fluorescence protein (GFP) and GAD65 into the lateral nucleus of the rat hypothalamus. Microinjection of 500 nl of AAV2 resulted in transduction of a 0.25±0.04 mm 3 with targeting errors of X=0.48 mm, Y=0.18 mm, Z=0.37 mm using standard stereotactic technique. Pre- and postinjection food and water consumption, urine and feces production, and weight were recorded. In comparison with rAAVCAGGFP- and PBS-injected animals, rats treated with rAAVCAGGAD65 demonstrated reduced weight gain (P<0.014) and transiently reduced daily food consumption (P<0.007) during the postoperative period. No changes in water consumption or waste production were recorded. Effective GAD65 gene transfer was confirmed with in situ hybridization using a probe to the woodchuck post-transcriptional regulatory element sequence included in the vector. These findings suggest that increased GABA production in lateral nucleus of the hypothalamus induced by GAD65 gene transfer may reduce weight gain through reduced feeding.